Plasma-neutral interactions in the lower thermosphere-ionosphere: The need for in situ measurements to address focused questions - Sarris, Theodoros; Palmroth, Minna; Aikio, Anita; Buchert, Stephan Christoph; Clemmons, James; Clilverd, Mark; Dandouras, Iannis; Doornbos, Eelco; Goodwin, Lindsay Victoria; Grandin, Maxime; Heelis, Roderick; Ivchenko, Nickolay; et al. (Frontiers in Astronomy and Space Sciences, 2023)
The lower thermosphere-ionosphere (LTI) is a key transition region between Earth’s atmosphere and space. Interactions between ions and neutrals maximize within the LTI and in particular at altitudes from 100 to 200 km, which is the least visited region of the near-Earth environment. The lack of in situ co-temporal and co-spatial measurements of all relevant parameters and their elusiveness to most remote-sensing methods means that the complex interactions between its neutral and charged constituents remain poorly characterized to this date. This lack of measurements, together with the ambiguity in the quantification of key processes in the 100 to 200 km altitude range affect current modeling efforts to expand atmospheric models upward to include the LTI and limit current space weather prediction capabilities. We present focused questions in the LTI that are related to the complex interactions between its neutral and charged constituents. These questions concern core physical processes that govern the energetics, dynamics, and chemistry of the LTI and need to be addressed as fundamental and long-standing questions in this critically unexplored boundary region. We also outline the range of in situ measurements that are needed to unambiguously quantify key LTI processes within this region, and present elements of an in situ concept based on past proposed mission concepts.